Mensuração dos custos em uma cadeia de exportação com uso de carga conteinerizada: análise sob a ótica da empresa exportadora - Gadelha, Caio de Araújo Pereira (2020)
Extensive foreign trade is one of the main reasons for the development of a country, as it directly influences the gross domestic product (GDP) and, consequently, the life of the population, providing jobs. The reduction of commercial costs is essential to promote the internationalization of production. Countries that achieve the proper development of their logistics and eliminate trade barriers between them will position themselves in international markets. In this context, this study aims to measure the costs of a containerized cargo export process, using the combination of the SCOR and ABC methods, from the perspective of an exporting company. Data collection was carried out through the application of semi-structured interviews and analysis of documents and, in possession of these, the process was structured and subsequently validated by the interviewees. In this way, it was necessary to map the export process sector, specifically the ceramic cargo, through identification of the agents responsible for the export process, apply the logistical approach Reference model of supply chain operations (SCOR ), which is a reference model of operations in the supply chain that allows to systematically structure the ceramic export process, model the process using the Bizagi Modeler software and the Business Process Management Notation (BPMN) notation, which allows a modeling flexible, intuitive, with the visualization and understanding of the activities that are performed by the chain and survey the activities and resources involved in order to structure the activity based costing methodology (ABC). Thus, it was possible to survey the dictionary of activities and the resources used, in order to structure the costs with the use of the ABC methodology, in the sectors of purchasing, planning and control of production, production, packaging and shipping. Subsequently, the costs of the logistics chain were found, as well as the segregation of the logistics costs, which correspond to approximately 28% of the total costs, being 17% of the logistics cost of transportation, 4% of storage, 2% of handling, 2% of management and administration, 2% packaging and 1% buying and selling.